Smart Governance in Indonesian Village Towards SDGs Achievement - Adelia Oktarina; Cita Pertiwi; Andi Risdawati Alwi Paluseri; Muhammad Fazri; Febrina Elia Nababan; Marthella Rivera Roidatua; Dian Karinawati Imron (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
After the COVID-19 pandemic, there has been an increase of digital technology adoption in the community, both in terms of its utilization and intensity. Digital Indonesia 2022 data released by We Are Social with Kepios shows an increase of 1 percent or 2.1 million internet users in January 2022 compared to January 2021 with increasing diverse internet usage variations. Digital transformation not only occurs in urban but also in rural areas. BPS data shows that the growth of internet users in villages is greater than in cities in 2020. This changing habit from the community encourages the village government to transform services and village development through smart governance. This research aims to describe the role of smart governance in supporting the achievement of sustainable development goals. This research was conducted by descriptive analysis using various works of literature as data. Various data show that smart governance encourages the creation of a village digital database, which is then used in the planning and decision-making process. During a pandemic, smart governance supports population administration services through features and application development. The results of the analysis conclude that smart governance generally drives the 17 goals of the SDGs, but particularly propels the achievements of SDGs' goals 16 and 17.